Perturbation Bound for the Eigenvalues of a Singular Diagonalizable Matrix. Issue 1 (February 2014) - Wei, Yimin; Qu, Yifei
Abstract: In this short note, we present a sharp upper bound for the perturbation of eigenvalues of a singular diagonalizable matrix given by Stanley C. Eisenstat [3].